2021
DOI: 10.18502/jfrh.v15i1.6075
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Aerobic Training and Crocin Consumption on Doxorubicin-Induced Testicular Toxicity in Rats

Abstract: Objective: Doxorubicin (DOX) treatment has been reported to increase the risk of serious toxicity in testis, therefore the aim of the present study was to investigate the antioxidant effects of training and Crocin on doxorubicin-induced testicular toxicity in rats. Materials and methods: In this experimental study, 42 Wistar rats were randomized into seven groups of six rats, including 1) Control, 2) DOX, 3) DOX + 10 mg/kg/d (day) Crocin, 4) DOX + 50 mg/kg/d Crocin, 5) DOX + high intensity interval train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…During HIIT, blood lactate levels increase from about three mmol in rats to 10 -15 mmol (18). Therefore, it seems that in this study, the increase in LHR gene expression is associated with the increase in lactate levels due to HIIT, and the positive expression of this gene is associated with increased Crocin is one of the active ingredients of saffron, which contains carotenoids that have anti-inflammatory and an-tioxidant effects on testicular tissue by increasing the total antioxidant capacity (13). The observed positive results of supplementation on DOX-induced side effects may be due to the same antioxidant and inflammatory effects (5-7).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…During HIIT, blood lactate levels increase from about three mmol in rats to 10 -15 mmol (18). Therefore, it seems that in this study, the increase in LHR gene expression is associated with the increase in lactate levels due to HIIT, and the positive expression of this gene is associated with increased Crocin is one of the active ingredients of saffron, which contains carotenoids that have anti-inflammatory and an-tioxidant effects on testicular tissue by increasing the total antioxidant capacity (13). The observed positive results of supplementation on DOX-induced side effects may be due to the same antioxidant and inflammatory effects (5-7).…”
Section: Discussionmentioning
confidence: 51%
“…It seems that Cr consumption and training can establish a balance in the cellular defense system against the oxidative state previously known to be induced by DOX in testicular tissues (13,21). Also, by reducing apoptosis, they provide a condition in favor of the anti-apoptotic system to increase LHR expression and thus spermatogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies have shown that oral Cr is hydrolyzed to crocetin in order to facilitate absorption in the intestine, which enters the liver quickly and in large amounts (8), which may jus-tify its effectiveness. Similarly, the lack of significant differences between the Cr and training group with the Cr group alone can be justified by the fact that sometimes antioxidant supplementation can stop the adaptations resulting from physical activity (29). According to our study results, using Cr and CT may not have produced more favorable synergistic effects than using Cr alone.…”
Section: Discussionmentioning
confidence: 54%